Pengaruh Kepemimpinan, Komitmen dan Motivasi Terhadap Kinerja Dosen Universitas - Rayu Sri Wahyuni; Budhi Atmadi; Masniarty Siagian; Nanda Destilan Sepada Harahap; Lilis Marini Elsera Tambunan; Musmuliadi; Eddi Suprayitno; Supar Wasesa; Efendy Sadly (Journal of Trends Economics and Accounting Research, 2023)
This research aims to determine the influence of leadership, commitment and motivation on lecturer performance at Medan Microskills University, both simultaneously and partially. This research uses a population, where the subjects of this research are 40 permanent lecturers at Medan Mikroskil University. The analysis used to test this research hypothesis is multiple linear regression analysis. Based on the research results of the First Hypothesis, Leadership and Motivation partially have a significant effect on the performance of Lecturers at Mikroskil University Medan, while commitment has no effect on Lecturer Performance at Mikroskil University Medan. Simultaneously, leadership, commitment and motivation have a significant effect on lecturer performance at Medan Mikroskil University. The Adjusted R Square value of 77.6% means that Lecturer Performance can still be explained by Leadership Quality, Commitment and Motivation. Meanwhile, the remaining 22.4% was influenced by other variables not examined in this research.